Employment and welfare effects of the quota for disabled workers in Brazil - Gustavo de Souza (Federal Reserve Bank of Chicago, 2023)
I study the effect o f a q uota f or disabled workers o n t he l abor m arket a nd o n welfare. Using a task-based model, I show that the effect o f a q uota w ill d epend o n the productivity of disabled workers and their labor supply elasticity. I estimate the productivity of disabled workers using variation from inspections of the quota. I find that the quota increased the hiring of disabled workers, but it reduced wages and employment of non-disabled workers, suggesting that the quota reduced firms' productivity. I estimate the labor supply elasticity of disabled workers using heterogeneous exposure across regions. Using the model calibrated to the empirical estimates, I find t hat the quota for disabled workers decreased welfare by 0.33% and forced the government to increase marginal taxes. However, alternatively, a subsidy for disabled workers could increase welfare
Keywords: E6; H2; H5; 330; quota for disabled workers; disability insurance; fiscal policy